Brand Love and Experience to Accelerate Loyalty Through Attachment Theory in Generation Y and Z - Karimah, Salsa Amirul; Marsasi, Endy Gunanto (Sekolah Tinggi Manajemen IPMI, 2025)
This study aims to determine the relationship between brand image, satisfaction, experience, and loyalty mediated by attitude and brand love in generations Y and Z. This study adds the experience variable as a novelty in this study and Attachment Theory is used as the main theory. The method in this study uses a quantitative approach with a purposive sampling technique that produces 183 samples. This study found that brand image has a significant positive effect on satisfaction and attitude. The findings of this study indicate that brand love is significantly positively influenced by satisfaction, attitude, and experience. Loyalty is significantly positively influenced by brand love. This study is expected to be useful for companies about various aspects that can encourage brand love and experience in social commerce platform users. This study is then expected to be able to support companies in channeling contributions to marketing strategies and tactics.